EthnoFilm: cinema-school and ethno-laboratory - Ivan Golovnev (EtnoAntropologia)
The paper is dedicated to the EthnoFilm educational project in the historical and modern context of visual anthropology. The EthnoFilm project intended as the educational ethnocultural initiative, aimed to attraction of interested youth to ethnographic research and video fixation of the unique cultural phenomena of the peoples of Arctic and Subarctic regions: Nenets, Khanty, Mansi, Komi. The first stage of the project, consisted of lectures and seminars, was considered as development of traditional positions of ethnography as well as visual forms of description of ethnic groups. The courses regarding film production, dramatic art, editing, filming were delivered. The basic attention was paid to individual lessons that had been related to working out of creative sketches and plans of realization of the future films as final works of project's participants. The central stage of the project was the “field film-school”, ethnographic and film practice in the form of expeditions towards the places of residence of the various indigenous communities. During the expeditions the ethnographic material has been gained and first editing of the received materials at portable montage studio has been made. Besides, the film draft version accompanied with a language translation and updating of film details has been showed to protagonists of shootings. This process involved into account the opinion of participants from the national environment. The final stage of the EthnoFilm project was considered as editing of the film almanac. Almanac’s films were united by a project's theme. On another hand, all the films were considered as individual works: the film’s style and content depended upon the chosen characters, environment and author's position.